Perancangan Prototype Bahan Ajar Tema Jembatan Ampera dan Sungai Musi Materi Pembagian Kelas II Sekolah Dasar - Antari, Luvi; Muslimin, Muslimin; Rohman, Rohman (Universitas Muhammadiyah Palembang, 2021)
Mathematics materials in elementary schools generally contain all basic knowledge about mathematics lessons at the school level. Counting operations are the initial concepts of mathematics that must be instilled in students. Division is one of the four main arithmetic operations whose concepts must be mastered by students as a way to maximize mathematical literacy skills at a further level. This study aims to produce a prototype 1 teaching material on multiplication material for grade II elementary school students who are taught thematically. Teaching materials are arranged using the theme of the city of Palembang which is close to the lives of students. This research is an early stage of development research. The research subjects were students of class II MI Hijriah II Palembang. The process of developing teaching materials is the preliminary stage, and the prototyping stage. Teaching materials are developed at the preliminary stage, namely the preparation of concepts that have not been mastered by students, planning on the basis of concepts that are still not mastered by students, determining competency standards, basic competencies, indicators, syllabus, lesson plans, determining the elements of teaching materials, collecting materials, compiling draft materials teach, test one to one and expert review. From the design of this prototype, the first prototype of teaching materials for integer arithmetic operations was produced for class II Madrasah Ibtidaiyah